Relationship between viruliferous Bemisia tabaci population and disease incidence of Pepper yellow leaf curl Indonesia virus in chili pepper - I GEDE RAI MAYA TEMAJA; DEWA GEDE WIRYANGGA SELANGGA; TRISNA AGUNG PHABIOLA; KHAMDAN KHALIMI; LISTIHANI LISTIHANI (Society for Indonesian Biodiversity, 2022)
Abstract. Temaja IGRM, Selangga DGW, Phabiola TA, Khalimi K, Listihani L. 2022. Relationship between viruliferous Bemisia tabaci population and disease incidence of Pepper yellow leaf curl Indonesia virus in chili pepper. Biodiversitas 23: 5360-5366. Bemisia tabaci Genn is an important pest in horticulture crops. Until today, B. tabaci has always been found in chili pepper and causes damage. In addition to a direct injury to the chili pepper, it is also the vector of Begomovirus. There is no research till date regarding the relationship between B. tabaci with Begomovirus which caused damage to chili pepper crops. Thus, the aim of this research was to analyze the interaction between B. tabaci population with the disease incidence of Begomovirus on chili peppers crops, as well as the percentage of viruliferous B. tabaci. This research noted B. tabaci population dynamics, disease incidence of pepper yellow leaf curl disease, and the percentage of viruliferous B. tabaci via PCR by using Begomovirus universal primer and DNA analysis confirmation. The highest imago population occurred at 6 WAP with the average density 27.21 imago/yellow sticky card, while the highest nymph population occurred at 8 WAP with the average density of 4.26 nymph/leaf. The high population of B. tabaci nymph and imago caused the incidence of Begomovirus disease to reach 83.07% at 12 WAP. Result showed that high population of B. tabaci accelerated the speed of virus in the field. The confirmation result of Begomovirus in B. tabaci body showed that the virus was Pepper yellow leaf curl Indonesia virus (PYLCIV). The highest homology obtained was between PYLCIV isolates from Sekaan, Bangli with isolates from Bayung Gede, Bangli which ranged from 99.6 to 99.8%. Further phylogenetic analysis showed that PYLCIV isolates from Sekaan, Bali formed a group with the isolate from Bayung Gede, Bangli, which was from a different group with other isolates. This proved that B. tabaci carries and transmits PYLCIV to chili peppers in Bali.